Influence of spray drying process on the quality of avocado powder: a functional food with great industrial potential - MARULANDA, Alejandra; RUIZ-RUIZ, Marilza Piedad; CORTES-RODRIGUEZ, Misael (Vitae, 2018)
Background: Colombia is the fifth largest producer of avocado and its agribusiness chain lacks value-added diversified products; therefore, at the governmental level, there has been promotion of internationalization policies aimed at opening up new markets and innovation with improved technology and food consumption patterns. The spray drying is an alternative conservation for avocado, a highly perishable fruit. Objectives: the aim of this study was to optimize the spray drying process for obtaining Hass avocado powder with better physicochemical properties and processing. Methods: an experimental design “Optimal” was used in the response surface methodology based on four factors: (A) maltodextrin (MD) concentration (2.81 to 11.25% w/w), (B) air inlet temperature (140-160°C), (C) outlet air temperature (80-90°C) and (D) atomizer disk speed (20000-26000 rpm). Results: the response variables where statistically significant differences (p<0.05) were found including: moisture, water activity, solubility, color coordinates (L*, a*, b*) hygroscopicity, wettability, extractable oil and deposit formation versus factors studied. Optimized value factors were: (A) 6.93% (B) 160°C (C) 84°C and (D) 26000 rpm. Conclusions: the experimental process optimization is presented as an effective tool for agribusiness, which improves product quality in terms of the factors that affect it, and in the case of avocado, allows the development of new value-added products, with potential uses in the food industry, pharmaceutical, cosmeceutical, among others.